2013
DOI: 10.1515/jpem-2012-0082
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hypothyroidism caused by a novel mutation of the dual oxidase 2 (DUOX2) gene

Abstract: The dual oxidase 2 (DUOX2) mutation results in an impairment of the hydrogen peroxidase-generating system and is identified as a dyshormonogenic cause of congenital hypothyroidism (CH). Here, we describe two unrelated Japanese girls with CH due to a novel DUOX2 mutation. They had high serum thyrotropin levels and low free thyroxine/thyroxine concentrations during the neonatal period. A novel missense mutation with a transversion of G to A at position 1462 in exon 12 of the DUOX2 gene that caused a replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…This recent study also suggested the involvement of a monoallelic variant of DUOX2 in the development of transient CH. Other reports have shown that biallelic DUOX2 mutations cause mild to moderate CH (13,14,15,16,19,22,30). Recently, some studies have shown that DUOX2 defects are the predominant cause of CH associated with dyshormonogenesis (13,14,15,16,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…This recent study also suggested the involvement of a monoallelic variant of DUOX2 in the development of transient CH. Other reports have shown that biallelic DUOX2 mutations cause mild to moderate CH (13,14,15,16,19,22,30). Recently, some studies have shown that DUOX2 defects are the predominant cause of CH associated with dyshormonogenesis (13,14,15,16,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors established the first genetic cause for transient CH with mono-allelic inactivation of DUOX2 and postulated that DUOX2 biallelic mutations would be associated with a permanent form of CH. However, numerous subsequent studies provide further evidence that the permanent or transient nature of congenital hypothyroidism is not directly related to the number of inactivated DUOX2 alleles, suggesting the existence of other pathophysiological factors [95][96][97][98].…”
Section: Duox Defects In Congenital Hypothyroidismmentioning
confidence: 99%
“…Eleven known causative genes of primary CH ( DUOXA2 , DUOX2 , FOXE1 , IYD , NKX2-1 , PAX8 , SLC5A5, SLC26A4, TG , TPO , and TSHR ) and 2 candidate genes ( DUOX1 and DUOXA1 ) were analyzed using a next-generation sequencer MiSeq (Illumina Inc., San Diego, CA, USA) following the protocol of SureSelect (Agilent Technologies, Santa Clara, CA, USA) as described previously [22]. Presences of mutations called by next-generation sequencing were confirmed by conventional PCR-based Sanger sequencing.…”
Section: Case Reportmentioning
confidence: 99%